2020
DOI: 10.1080/19768354.2020.1818618
|View full text |Cite
|
Sign up to set email alerts
|

CD47 (Cluster of differentiation 47): an anti-phagocytic receptor with a multitude of signaling functions

Abstract: CD47 is a tumor-associated antigen best known for its ability to bind counter-receptors on the surface of professional phagocytes as an immune-evasion strategy. Recently, CD47 has been shown to play a role as a signaling receptor, involving a number of cell physiological processes. This review provides a comprehensive survey of the signaling pathways triggered by CD47 ligand-mediated cell death in tumor cells. Such an understanding should lead to improvement of CD47-targeted anti-tumor therapeutics able to bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…CD47 is not only a receptor for SIRP and the matricellular protein thrombospondin-1 (TSP-1), but also for ligands that are emerging [ 40 ]. Evidence has indicated that CD47 is a versatile factor in cell activity, such as in angiogenesis [ 41 , 42 ], cell migration, immune-cell filtration [ 43 ], as well as cell death [ 44 ]. In CD47 deficient mice, angiogenesis in xenograft tumor was enhanced, and the lack of CD47 accelerated tumor progression [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…CD47 is not only a receptor for SIRP and the matricellular protein thrombospondin-1 (TSP-1), but also for ligands that are emerging [ 40 ]. Evidence has indicated that CD47 is a versatile factor in cell activity, such as in angiogenesis [ 41 , 42 ], cell migration, immune-cell filtration [ 43 ], as well as cell death [ 44 ]. In CD47 deficient mice, angiogenesis in xenograft tumor was enhanced, and the lack of CD47 accelerated tumor progression [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the gene for the transmembrane protein CD47 showed the highest upregulation after 75 s, followed by a significant downregulation after 15 min hypergravity. CD47 is an anti-phagocytic receptor with a multitude of signaling functions including calcium signaling (reviewed in [77]). Calcium signaling plays an important role in altered gravity and has been described for various cell types (reviewed in [78]).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of CD47 on tumor cells can also lead to caspase-independent cell death induction, although the exact molecular mechanisms are still not completely understood [ 116 ]. Therapeutic approaches currently focus on inhibiting the CD47-SIRPa binding to activate phagocytosis of cancer cells and several small and large molecule inhibitors are undergoing clinical investigations.…”
Section: Immunological Based Therapies In Hccmentioning
confidence: 99%